The Impact of Knowledge Management Process and Intellectual Capital on Entrepreneurial Orientation and Innovation - Yu, Qi; Aslam, Sumaira; Murad, Majid; Jiatong, Wang; Syed, Nausheen (Frontiers in Psychology, 2022)
Innovation is considered to be a dominant cause for sustainable business success. Knowledge management and intellectual capital are powerful tools to promote innovation in the organization. Therefore, this study aims to explore the influence of knowledge management process and intellectual capital on innovation with the mediating effect of entrepreneurial orientation and moderating role of leader education level. Data was collected from a sample of 393 IT firms listed in the Pakistan Software Houses Association and applied a partial least squares structural educational modeling (SEM) technique. The results show that the knowledge management process and intellectual capital have a positive effect on innovation. Moreover, the study confirms that entrepreneurial orientation partially mediates in the relationship between knowledge management and intellectual capital on innovation. Furthermore, the moderation effect of leader’s education was confirmed for knowledge management-innovation relationship whereas, the moderation effect of leader’s education for intellectual capital and innovation relationship was insignificant. Recommendations for practitioners and future research directions were also discussed.